2012
DOI: 10.1155/2013/586136
|View full text |Cite
|
Sign up to set email alerts
|

Sorption of Uranium(VI) and Thorium(IV) by Jordanian Bentonite

Abstract: Puri�cation of raw bentonite was done to remove quartz. is includes mixing the raw bentonite with water and then centrifuge it at �50 rpm; this process is repeated until white puri�ed bentonite is obtained. �RD, �RF, FTIR, and SEM techniques will be used for the characterization of puri�ed bentonite. e sorption behavior of puri�ed Jordanian bentonite towards UO 2 2+and  4+ metal ions in aqueous solutions was studied by batch experiment as a function of pH, contact time, temperature, and column techniques at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…The adsorption isotherms and kinetics commonly used are listed in Table 1. In addition, most of the adsorption of ions on clays and oxides are best described by Langmuir, Dubinin-Radushkevich and Freundlich isotherm models and Pseudo-secondorder kinetic model [47][48][49][50][51][52][53].…”
Section: Adsorption and Kinetic Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The adsorption isotherms and kinetics commonly used are listed in Table 1. In addition, most of the adsorption of ions on clays and oxides are best described by Langmuir, Dubinin-Radushkevich and Freundlich isotherm models and Pseudo-secondorder kinetic model [47][48][49][50][51][52][53].…”
Section: Adsorption and Kinetic Modelsmentioning
confidence: 99%
“…In the another study, bentonite was effectively used to remove thorium (IV) at pH 3, equilibration time of 18 h and 25°C and adsorption was fitted to Freundlich, Langmuir and Dubinin-Radushkevich isotherm models. Desorption experiment shows that thorium (IV) is best recovered with 1.0 M HNO 3 [49]. However, the use of bentonite for sorption of heavy metals has some negative effect.…”
Section: Bentonitementioning
confidence: 99%
“…The latter study showed how U 6+ "preferred" to sorb to kaolinite and not to humic acid that was directly bound to a clay surface [30]. The upscaling of the removal of U 6+ by sorption, can be investigated in static or dynamic mode [10]. In the latter, binders are required to avoid permeability problems associated to flow rate (Q) in the columns.…”
Section: +mentioning
confidence: 99%
“…Separation processes from liquid to solid are therefore getting relevance for the treatment of leachates from landfills or mining tails as significant amounts of water can be treated in order to reach legislation thresholds for discharges. , among them co-precipitation, membrane filtration and sorption [9][10][11].…”
mentioning
confidence: 99%
See 1 more Smart Citation